Evaluation of digital competence of a secondary educational organization based on the DigCompOrg model - Fernández Miravete, Ángel David; Prendes Espinosa, Mª Paz (Revista Complutense de Educación, 2021)
The European Framework for Digitally Competent Educational Organizations (DigCompOrg) aims to support educational organizations to proceed with their digitization in a systematic and strategic way. This paper presents an evaluative investigation on the degree of development of digital competence in a secondary school (case study) from the dimensions collected in this model. The research design is based on the ADDIE model. We opted for a mixed method that combines quantitative data collection techniques (SELFIE questionnaire) and qualitative (semi-structured interviews, discussion group and participant observation). The results presented in this article take into account the quantitative information collected among the main educational agents: school leaders, teachers and students. Starting from the first stage of needs analysis, different actions and improvement strategies are then proposed that allow the school to advance as a digitally competent organization. Among the main conclusions it is shown that more efforts are invested in promoting practices aimed at the teaching and learning process in students or teacher training, postponing other areas such as leadership and governance or evaluation practicescompetencia digital
Keywords: digital competence; secondary education; case study; educational organization; technology of the information and communication